Influenza vaccine acceptance and hesitancy among adults hospitalized with severe acute respiratory illnesses, United States 2019–2020. Issue 37 (31st August 2021) - Lytle, Kelsey L.; Collins, Sean P.; Feldstein, Leora R.; Baughman, Adrienne H.; Brown, Samuel M.; Casey, Jonathan D.; Erickson, Heidi L.; Exline, Matthew C.; Files, D. Clark; Gibbs, Kevin W.; Ginde, Adit A.; Gong, Michelle N.; et al.
Highlights: Among 679 severely ill adults during the 2019–2020 influenza season, 38.9% were unvaccinated. Among those unvaccinated, 51.1% reported intentionally avoiding vaccination. Lack of insurance and being non-White or Hispanic were associated with not being vaccinated. Abstract: Introduction: Understanding patient factors associated with not being vaccinated is essential for successful implementation of influenza vaccination programs. Methods: We enrolled adults hospitalized with severe acute respiratory illness at 10 United States (US) hospitals during the 2019–2020 influenza season. We interviewed patients to collect data about influenza vaccination, sociodemographic characteristics, and vaccine perceptions. Results: Among 679 participants, 264 (38.9%) reported not receiving influenza vaccination. Among those not vaccinated, 135 (51.1%) reported choosing not to receive a vaccine because of perceived ineffectiveness (36.7%) or risk (14.4%) of influenza vaccination. Sociodemographic factors associated with not being vaccinated included no medical insurance (aOR = 6.42; 95% CI: 2.52–16.38) and being non-White or Hispanic (aOR = 1.54, 95% CI: 1.02–2.32). Conclusions: Optimizing uptake of influenza vaccination in the US may be improved by educational programs regarding vaccine safety and effectiveness and enhancing vaccine access, particularly among non-White and Hispanic Americans and those without medical insurance.